Ps 2,12: 'Küsst den Sohn!'? - Sabottka, Liudger (Biblica, 2006)
The long-standing difficulty in Ps 2,12 rba-w%q#$%;na is tentatively resolved by deriving w%q#$%;na from q#$n II – 'to be armed', and interpreting the verbal form according to Gesenius’ Hebrew Grammar, § 52h, as 'privative Piel': 'to be/get disarmed', whereas rba takes its normal meaning 'pure, sincere'.